Bi-allelic mutations in MOS cause female infertility characterized by preimplantation embryonic arrest. Issue 3 (6th January 2022) - Zeng, Yang; Shi, Juanzi; Xu, Shiru; Shi, Rong; Wu, Tonghua; Li, Hongyan; Xue, Xia; Zhu, Yuanchang; Chen, Biaobang; Sang, Qing; Wang, Lei
Abstract: STUDY QUESTION: Are mutations in MOS (MOS proto-oncogene, serine/threonine kinase) involved in early embryonic arrest in infertile women? SUMMARY ANSWER: We identified mutations in MOS that may cause human female infertility characterized by preimplantation embryonic arrest (PREMBA), and the effects of the mutations in human embryonic kidney 293T (HEK293T cells) and mouse oocytes provided evidence for a causal relation between MOS and female infertility. WHAT IS KNOWN ALREADY: MOS, an activator of mitogen-activated protein kinase, mediates germinal vesicle breakdown and metaphase II arrest. Female MOS knockout mice are viable but sterile. Thus, MOS seems to be an important part of the mammalian cell cycle mechanism that regulates female meiosis. STUDY DESIGN, SIZE, DURATION: Whole-exome sequencing, bioinformatics filtering analysis and genetic analysis were performed to identify two different biallelic mutations in MOS in two independent families. The infertile patients presenting with early embryonic arrest were recruited from October 2018 to June 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: The female patients diagnosed with primary infertility were recruited from the reproduction centres of local hospitals. Genomic DNA from the affected individuals, their family members and healthy controls was extracted from peripheral blood. We performed whole-exome sequencing in patients diagnosed with PREMBA. Functional effects of the mutations were investigated in HEK293T cells by western blotting and in mouse oocytes by microinjection and immunofluorescence. MAIN RESULTS AND THE ROLE OF CHANCE: We identified the homozygous missense mutation c.285C>A (p.(Asn95Lys)) and the compound heterozygous mutations c.467delG (p.(Gly156Alafs*18)) and c.956G>A (p.(Arg319His)) in MOS in two independent patients. The mutations c.285C>A (p.(Asn95Lys)) and c.467delG (p.(Gly156Alafs*18)) reduced the protein level of MOS, and all mutations reduced the ability of MOS to phosphorylate its downstream target, extracellular signal-regulated kinase1/2. In addition, the identified mutations reduced the capacity of exogenous human MOS to rescue the metaphase II exit phenotype, and the F-actin cytoskeleton of mouse oocytes was affected by the patient-derived mutations. LIMITATIONS, REASONS FOR CAUTION: Owing to the lack of in vivo data from patient oocytes, the exact molecular mechanism affected by MOS mutations and leading to PREMBA is still unknown and should be further investigated using knock-out or knock-in mice. WIDER IMPLICATIONS OF THE FINDINGS: We identified recessive mutations in MOS in two independent patients with the PREMBA phenotype. Our findings reveal the important role of MOS during human oocyte meiosis and embryonic development and suggest that mutations in MOS may be precise diagnostic markers for clinical genetic counselling. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Natural Science Foundation of China (81725006, 81822019, 81771581, 81971450, 81971382, 82001538 and 82071642), the project supported by the Shanghai Municipal Science and Technology Major Project (2017SHZDZX01), the Project of the Shanghai Municipal Science and Technology Commission (19JC1411001), the Natural Science Foundation of Shanghai (19ZR1444500 and 21ZR1404800), the Shuguang Program of the Shanghai Education Development Foundation and the Shanghai Municipal Education Commission (18SG03), the Foundation of the Shanghai Health and Family Planning Commission (20154Y0162), the Capacity Building Planning Program for Shanghai Women and Children's Health Service and the collaborative innovation centre project construction for Shanghai Women and Children's Health. The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.